2017
DOI: 10.7860/jcdr/2017/27258.10677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effect of Irrigants with or without Surfactant on Root Canal Transportation by Cone Beam Computed Tomography–An In vitro Study

Abstract: Instrumentation using irrigating solutions added with surfactant like 1% cetrimide maintained the canal curvature well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Irrigation for all specimens during root canal preparation was done by using of 5% of NaOCl to remove all debris during root canal instrumentaion, facilate insertion of rotary files with no stress and to provide clean root canal walls. Then final rinse was done using 17% EDTA solution to remove all smear layer which found during instrumentation which might cause more force on rotary file causing canal transportaion, this protocol was aggreged with Nazari Moghadam et al (33). Moreover, Ahmed et al (34) reported in their study that canal transportation might occur due to the physical properties of rotary files or the type of irrigation used during root canal prepartion, which might cause change in micro hardness of dentin, softening and deminerlization of dentin, that might compromise the preservation of the natural shape of the canal which could lead to canal transportation.…”
Section: Discussionmentioning
confidence: 99%
“…Irrigation for all specimens during root canal preparation was done by using of 5% of NaOCl to remove all debris during root canal instrumentaion, facilate insertion of rotary files with no stress and to provide clean root canal walls. Then final rinse was done using 17% EDTA solution to remove all smear layer which found during instrumentation which might cause more force on rotary file causing canal transportaion, this protocol was aggreged with Nazari Moghadam et al (33). Moreover, Ahmed et al (34) reported in their study that canal transportation might occur due to the physical properties of rotary files or the type of irrigation used during root canal prepartion, which might cause change in micro hardness of dentin, softening and deminerlization of dentin, that might compromise the preservation of the natural shape of the canal which could lead to canal transportation.…”
Section: Discussionmentioning
confidence: 99%